A Review on Digital Marketing and Its Applications (International Journal of Innovative Research in Computer Science & Technology, 2022)
Digital marketing refers to any marketing  campaign that uses an electronic equipment or the net.  Organizations uses digital platforms such as search  engines, social media, email, or their website to  communicate with current and future consumers. 'Digital  advertising,' 'online marketing,' or 'internet advertising' are  other terms for it. The advertising of products or services  using digital technology, including the Internet, cellular  phones, displays marketing, as well as other electronic  content, is known as digital marketing. Digital marketing  has altered the way brands and businesses use technology  for advertising since the nineties or 2000s. As online  technologies become increasingly interwoven into  marketing tactics and everyday life, and as customers use  digital devices instead of visiting physical businesses,  digital marketing initiatives are becoming more prevalent  and effective. This document concentrates on gaining a  conceptual understanding of digital advertising, how it  helps today's organizations, and various case analysis as  examples.
Keywords: Businesses; Consumers; Digital Marketing; Social Media